Domestic duck production : science and practice - Cherry, P. 1937- (CABI, 2008)
This book contains chapters that discuss the history, biology, duck raising for meat and egg production, housing, growth, feeding, breeding, health and fertility. This book is intended as a practical guide for technical and advisory staff involved in both commercial and subsistence-level duck production, as a reference text for commercial producers and their professional staff and as a resource for undergraduate and postgraduate students.